Main factors that determine students´ level of proficiency in English Intermediate I of the Foreign Languages Department of the University of El Salvador during the semester II-2011 - Pérez González, Claudia Patricia; Orellana Villeda, Ingrid Mariela; Figueroa Urbano, Vicky Evangelina; Ortiz Rivera, Ana Blanca Guadalupe; Hernández Rivas, René Arturo; Garay Salinas, Ricardo (San Salvador, El Salvador : Universidad de El Salvador, 2012)
There are some factors that are important to determine students’ level of proficiency in English. Many authors have made different studies about how proficiency is influenced by some factors. One of these factors is personality, which is defined as one of the affective factors that are equally important for explaining differential success among second language learners (Brown, 2000). Another factor is the use of technology. According to Mary Masterson of Georgia stateUniversity (2011), some technological resourceslike projectors, computers and CD players are some tools that students can take into account to improve their proficiency in English. Some other authors state that background knowledge is important in defining students’ level of proficiency. Biemans and Simons’ (1996) defined background knowledge as all knowledge learners have when entering in a learning environment that is potentially relevant for acquiring new knowledge. Other authors state that learning strategies play an important role among second language learners. Oxford (1990) said that the use of learning strategies “make learning easier, faster, more enjoyable, more self-directed, more effective, and more transferable to new situations”. Scarcella and Oxford (1992) defined learning strategies as “specific actions, behaviors, steps, or techniques used by students to enhance their own learning”. Each of these factors may help to understand how proficiency is developed among students.
Incluye apéndices.
Tesis -- (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2012
Bibliografía : hoja 27-30
Audiencia general.
La tesis también está en formato digital.
Keywords: Inglés -- Enseñanza; Métodos de enseñanza; Estrategias de aprendizaje